1995
DOI: 10.1080/08327823.1995.11688266
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric Properties of Grapes and Sugar Solutions at 2.45 GHz

Abstract: Dielectric properties of grapes at 2.45 GHz were measured at moisture contents varying from 80 to 15% (wet basis) at temperatures ranging from 25-80 degrees C using the Open Ended Coaxial Transmission Line Technique. Both dielectric constant and loss factor decreased with decreasing moisture content. In low moisture samples these properties were found to be considerably influenced by higher temperatures. Dielectric properties of sugar solutions of varying concentrations (20-250% by weight in water) were also d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
30
0
4

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 1 publication
7
30
0
4
Order By: Relevance
“…Knutson et al (1988) reported the use of the microwave oven to pasteurize milk, and a continuous laboratory scale system has been successfully developed for this purpose (Kudra et al, 1991). Microwave heating is greatly affected by the presence of water in foods (Tulasidas et al, 1995) as water is the major absorber of microwave energy in food, consequently, the higher the moisture content, the better are the resultant heating effects. In contrast to conventional heating, microwaves penetrate the material, interact with it and generate heat leading to its rapid heating.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Knutson et al (1988) reported the use of the microwave oven to pasteurize milk, and a continuous laboratory scale system has been successfully developed for this purpose (Kudra et al, 1991). Microwave heating is greatly affected by the presence of water in foods (Tulasidas et al, 1995) as water is the major absorber of microwave energy in food, consequently, the higher the moisture content, the better are the resultant heating effects. In contrast to conventional heating, microwaves penetrate the material, interact with it and generate heat leading to its rapid heating.…”
mentioning
confidence: 99%
“…Materials containing polar molecules such as water are rapidly heated when exposed to microwave radiation due to molecular friction generated by dipolar rotation in the presence of an alternating electric field. It is also reported that dissolved sugars are the main microwave susceptors in high carbohydrate foods and syrups (Tulasidas et al, 1995). Since honey contains a substantial amount of water (18-24%) as well as large amounts of dissolved sugars (70-80%), microwave radiation could be effectively used for heating honey.…”
mentioning
confidence: 99%
“…For an aqueous system, although water is a good microwave absorber, its dielectric loss factor drops from above 20 to below 5 as the temperature rises from 3°C to 95°C 56,57 . On the other hand, in a study of grape and sugar solutions, the loss factors of low moisture grapes and high concentration sugar solutions rise as the temperature rises 58 . It has found that NaCl and CuSO 4 solutions have different dielectric responses to microwaves from that of pure water 59 .…”
Section: Study the Temperature Influence On The Microwave Effectsmentioning
confidence: 99%
“…En este sentido se han realizado numerosos estudios en alimentos (Van Dyke et al, 1969;Roebuck et al, 1972;To et al, 1974;Nelson, 1978a,b;Mudgett et al, 1980;Padua, 1993;Tulasidas et al, 1995;Bircan y Barringer, 1998;Funebo y Ohlsson, 1999;Kraszewski, 2000;Sipahioglu, 2002).…”
unclassified
“…Aplicación de la espectroscopia dieléctrica de microondas a productos de la agricultura Se ha estudiado la aplicación de microondas a diversas frutas y vegetales con la finalidad de correlacionar diferentes propiedades como son: humedad, contenido en almidón, y efecto de la temperatura con la variación de las propiedades dieléctricas (Nelson, 1980(Nelson, , 1983(Nelson, , 1992(Nelson, , 2005Tran et al, 1984;Seaman y Seals, 1991;Nelson et al, 1993Nelson et al, , 1994Berbert et al, 2002;Feng et al, 2002;Sharma y Prasad, 2002;Sipahioglu y Barringer, 2003;Datta et al, 2005;. Se han desarrollado varios modelos predictivos que correlacionan las propiedades dieléctricas de frutas y vegetales con algunos parámetros como la humedad, sólidos solubles e insolubles y temperatura (Sun et al, 1995;Tulasidas et al, 1995;Sharma y Prasad, 2002;Nelson, 2003;Sipahioglu y Barringer, 2003;Berbert et al, 2004;Calay et al, 2007). En general, cabe destacar que las frutas y verduras poseen una fase líquida importante que provoca que la constante dieléctrica adquiera valores altos; por el contrario, en frutas y verduras deshidratadas tanto la constante dieléctrica como el factor de pérdidas toman valores menores.…”
unclassified